Effect of the protective materials and water on the repairing quality of nickel aluminum bronze during underwater wet laser repairing. (June 2019) - Feng, Xiangru; Cui, Xiufang; Zheng, Wei; Lu, Bingwen; Dong, Meiling; Wen, Xin; Zhao, Yao; Jin, Guo
Highlights: The interactions between laser, water and target are not only destructive but also helpful to repair damaged parts. The as-repaired layers manufactured by underwater wet laser repairing process possesses good repairing quality. Smaller heat affected zone, smaller coating thickness and more deformation are obtained. Abstract: Today, many researchers focus on the destructive effects of the laser in underwater environment. In this paper, we present underwater wet laser repairing which is a kind of technique to avert the destructive effects of the interactions between laser, water and target. We introduce helpful materials to repair nickel aluminum bronze (NAB) plate and discuss the effect of interactions between the laser, water and target on the repairing quality during underwater wet laser repairing process. As a result, the useful materials, Zn and Ti, protect melting pool from damaging by the high-speed water jet and shock wave. The as-repaired layers possess good repairing quality. In addition, the as-repaired layer manufactured by underwater wet laser repairing process possesses smaller heat affected zone, smaller coating thickness and more deformation than the layer manufactured in the air. In summary, with the help of the useful materials, a good repairing quality can be obtained.